2015
DOI: 10.1002/ps.4059
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of GST genes from the Chinese white pine beetle Dendroctonus armandi (Curculionidae: Scolytinae) and their response to host chemical defence

Abstract: The increased transcription levels of GST genes suggested that they have some relationship with the detoxification of terpenoids that are released by host trees. The mediating oxidative stress that is caused by monoterpene might be the main role of the bark beetle GSTs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
37
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(40 citation statements)
references
References 59 publications
3
37
0
Order By: Relevance
“…We observed up‐regulation of genes in the B. xylophilus ‐specific clade of FMOs (FMO‐5, FMO‐10). Although many GST (Dai et al, ), UGT (Ono & Tsuruoka, ), ABC transporter (Yazaki, ) and cuticle collagen (Bongers, ) gene families are also associated with metabolism of xenobiotics, these gene families were not expanded in B. xylophilus compared to xenobiotic terpene metabolism pathway genes. Previous studies have found that certain genes in the α‐pinene‐treated samples were up‐regulated, including CYPs, SDRs, UGTs and GSTs (Li et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…We observed up‐regulation of genes in the B. xylophilus ‐specific clade of FMOs (FMO‐5, FMO‐10). Although many GST (Dai et al, ), UGT (Ono & Tsuruoka, ), ABC transporter (Yazaki, ) and cuticle collagen (Bongers, ) gene families are also associated with metabolism of xenobiotics, these gene families were not expanded in B. xylophilus compared to xenobiotic terpene metabolism pathway genes. Previous studies have found that certain genes in the α‐pinene‐treated samples were up‐regulated, including CYPs, SDRs, UGTs and GSTs (Li et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The use of very similar experimental strategies with the other detoxifying enzymes (P450 enzymes and GSTs) of D. armand enabled the identification of CarE genes probably involved in similar functions . DaCarE s maintain higher transcript levels in larvae and adults that need to hydrolyze a host secondary metabolite or degrade an odorant .…”
Section: Discussionmentioning
confidence: 99%
“…For instance, monoterpenoids from Euphorbia ebracteolata showed an inhibitory effect against human carboxylesterase‐2 (hCE‐2) using a fluorescence bioassay in vitro . However, monoterpene treatment for Scolytidea focuses on CYP gene inducement . Upon treatment with monoterpenes and turpentine, DaCarE1 , DaCarE2 and DaCarE5 were downregulated in adults, unlike another two detoxifying enzymes, and there is no specificity for xenobiotics in them.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations